2021
DOI: 10.1016/j.chemosphere.2020.128986
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of dose-range glyphosate on locomotor behavior, neuronal activity, glio-cerebrovascular structures, and transcript regulations in zebrafish larvae

Abstract: Highlights1. In zebrafish larvae, behavioral and brain electrophysiological defects elicit at high glyphosate concentrations.2. Neurological outcomes are not associated with structural neuro-vascular or muscular malformations.3. Morphological signs of microglia activation are reported after exposure to low and high glyphosate concentrations.4. Transcriptomic analysis reveals the deregulation of candidate pathways, possibly extending to neuronal vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 63 publications
0
13
0
1
Order By: Relevance
“…Morphological parameters were measured at 120 hpf for zebrafish exposed to 0.1, 0.5, 1 and 10 μg/L of cocktail pesticide (duplicate, n=10/group) as we previously described (Forner-Piquer et al, 2020). Mortality rate at 24 hpf and cumulative hatching at 96 and 120 hpf were also evaluated (duplicate, n = 200/group).…”
Section: Zebrafish Locomotor Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological parameters were measured at 120 hpf for zebrafish exposed to 0.1, 0.5, 1 and 10 μg/L of cocktail pesticide (duplicate, n=10/group) as we previously described (Forner-Piquer et al, 2020). Mortality rate at 24 hpf and cumulative hatching at 96 and 120 hpf were also evaluated (duplicate, n = 200/group).…”
Section: Zebrafish Locomotor Activitymentioning
confidence: 99%
“…Mortality rate at 24 hpf and cumulative hatching at 96 and 120 hpf were also evaluated (duplicate, n = 200/group). In zebrafish, 120 hpf larvae from control and 10 µg/L cocktail groups were stained using Phalloidin-iFluor 594 (muscle fibers; Abcam ab176757) in duplicate, n=10/group; see (Forner-Piquer et al, 2020). For in vivo 2-photon brain analyses, 96-hpf Tg(fli1a:GFP)y1Tg (duplicate, CTR n=15, 10 μg/L n=10) and Tg(HuC:Tomato) (duplicate, CTR n=10, 10 μg/L n=5) transgenic zebrafish larvae were studied as we previously described (Forner-Piquer et al, 2020).…”
Section: Zebrafish Locomotor Activitymentioning
confidence: 99%
“…There is evidence that this compound can reach surface waters via direct applications and runoffs. Limits for the presence of GLY in drinking water range from the highest levels in Australia (1000 µg/L) and USA (700 µg/L) to lower levels in Canada (280 µg/L) and Europe (0.1 µg/L) [ 2 ]. Despite the claim that GLY-based herbicides only target plant-specific enzymatic pathway, various studies demonstrated adverse effects of this contaminant in both vertebrate and invertebrates [ 3 , 4 , 5 ], as well as in wildlife and aquatic species [ 6 , 7 , 8 , 9 , 10 ], where this contaminant, alone or in formulation, induced oxidative stress and DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…47 6 dpf is the earliest timepoint at which zebrafish exhibits maximal spontaneous locomotion. 48 Thus, to assess if SvMEs can relieve this symptom, we performed the behavioral assessment on zebrafish larvae at above time.…”
Section: Resultsmentioning
confidence: 99%